PTC electric heating composite paper and preparation method thereof
By adopting a double-layer structure, the combination of conductive components, polymer resin and fiber materials for wet papermaking is solved, and the block resistance of existing PTC electrothermal materials is achieved, and the production cost is reduced.
Patent Information
- Application Number
- CN202411929237.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-28
AI Technical Summary
The block resistance of existing PTC electrothermal materials is too large, making it difficult to achieve sufficient surface power density under low voltage drive, increasing the complexity of electrode design and production costs.
PTC electrothermal composite paper adopts a double-layer structure. The first layer is a nonwoven sheet material, and the second layer contains conductive components, polymer resin, organic crystal material and fiber material for wet papermaking. Through material distribution across scales, low block resistance is achieved while ensuring PTC strength.
It achieves a low block resistance, ensures the mechanical strength and microstructure stability of PTC electrothermal composite paper, reduces production costs, and adapts to material molding and manufacturing of different scales.
Smart Images

Figure CN119729923A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrothermal material preparation, and in particular to a PTC electrothermal composite paper and a preparation method thereof. Background Art
[0002] PTC is the abbreviation of Positive Temperature Coefficient, which means positive temperature coefficient. PTC materials are often used as self-temperature-controlled electric heating materials because of their characteristic that the resistance increases with the increase of temperature. PTC electric heating materials are divided into two categories: inorganic and organic materials. Organic PTC materials are soft and bendable, have good plasticity, and can be made into thin and large-area sheet materials, which should be widely used. Organic PTC materials are usually made of organic polymers with conductive fillers added. In order to obtain better PTC strength (PTC strength = R max / R 20 , Rmax is the maximum resistance value, R20 is the resistance value at 20℃), usually the amount of conductive filler added is required to be near the percolation threshold. Near the percolation threshold, the resistivity of the material is usually large, which leads to the block resistance being too large for large-area sheet heating materials. When PTC heating sheet materials with too large block resistance are used as electric heating applications, it is very necessary to obtain sufficient surface power density (Surface Power Density, referred to as SPD) to meet application needs. Here we simplify the assumption of a rectangular heating plate with a block resistance of Rs, two parallel electrodes on both sides, the inner spacing of the electrodes is L, the width of the other side of the heating plate is W, and the voltage applied to both ends of the electrodes is U. A formula can be derived to illustrate:
[0003] Total resistance of heater R = Rs*L / W (1)
[0004] Power P = U^2 / R (2)
[0005] Surface power density SPD = P / (L*W) (3)
[0006] Substituting equations (2) and (1) into equation (3), we obtain
[0007] SPD=U^2 / (Rs*L^2) (4)
[0008] From formula (4), it can be seen that if the square resistance Rs is very large, the SPD will be very small and will not meet the use requirements. At this time, to ensure sufficient SPD, it can be achieved by increasing the voltage U or reducing the electrode spacing L. However, for many electric heating applications, the electric heater cannot be made too narrow. In order to achieve a small electrode spacing, the electrodes usually need to be made into a complex forked finger shape. Moreover, the larger the square resistance Rs is, the higher the SPD requirement is, and the denser the forked finger electrodes need to be, which increases the production cost and process complexity of the electric heater. At present, the PTC electric heating films sold on the market are all forked finger electrodes (some say they are made into grid lines or use etched circuit board electrodes, which are the same meaning), and many are designed to be very dense. In addition, according to formula (4), the voltage U can also be increased to compensate for the defect of too large Rs, but the voltage U cannot be too large. The ordinary household voltage is 220V, and some areas that require special safety also require the voltage to be below 36V. Patent 201910720440.7 discloses a PTC electric heating film driven by a low voltage of 36V or less and a preparation method thereof, which claims that voltage drive can be achieved. Figure 2 The drawing also shows only two simple conductive copper strips (without the complex design of the interdigital electrodes), but by observing its embodiment, it can be found that its square resistance is 4000Ω / sq-8000Ω / sq, which is still very large. According to Formula 4, assuming that the voltage is selected to be 36V, the power density for the PTC heating heater is at least 300W / m2, and the square resistance is taken as a small 4000Ω / sq. Calculated in this way, the electrode spacing L is 3.3cm. Such a narrow heater lacks practical value in many application fields.
[0009] Based on the above, in order to realize a PTC heating sheet with simple electrode design and truly suitable for low-voltage drive, the core contradiction to be solved is the need to achieve lower sheet resistance while ensuring a certain PTC strength, and the existing technology has not yet solved this problem. Summary of the invention
[0010] In view of the deficiencies in the prior art, the present invention provides an electric heating sheet with low sheet resistance and certain PTC strength, specifically a PTC electric heating composite paper and a preparation method thereof.
[0011] The technical solution adopted by the present invention is: a PTC electrothermal composite paper, including a first layer structure 2 and a second layer structure 22, the first layer structure 2 is a non-woven sheet material, and the second layer structure 22 includes a conductive component, a polymer resin, an organic crystal material and a fiber material for wet papermaking.
[0012] Preferably, the second layer structure 22 further comprises chopped carbon fiber material.
[0013] A method for preparing PTC electrothermal composite paper comprises the following steps:
[0014] (1) preparing materials according to the following components: non-woven sheet material, conductive component, polymer resin material, organic crystal material and fiber material for wet papermaking;
[0015] (2) preparing an aqueous dispersion of an organic crystalline material;
[0016] (3) preparing an aqueous dispersion of a conductive component;
[0017] (4) preparing an aqueous dispersion of a fiber material for wet papermaking;
[0018] (5) mixing the aqueous dispersion of the conductive component, the aqueous dispersion of the organic crystal material, the polymer resin material, and the aqueous dispersion of the wet papermaking fiber material, and stirring them thoroughly to form a mixed slurry;
[0019] (6) spreading the nonwoven sheet material on a forming wire of a paper machine;
[0020] (7) Papermaking, the mixed slurry is transported to the surface of the non-woven sheet material, and under the vacuum suction force of the paper machine, the water in the mixed slurry is filtered out through the non-woven sheet material, and the solid insoluble matter in the mixed slurry is left on the surface of the non-woven sheet material;
[0021] (8) Drying to remove residual moisture to obtain a PTC electrothermal composite paper, which includes a first layer structure 2 and a second layer structure 22. The first layer structure 2 is a non-woven sheet material, and the second layer structure 22 includes a conductive component, a polymer resin, an organic crystal material, and a fiber material for wet papermaking.
[0022] Preferably, the non-woven sheet material in step (1) is non-woven fabric or paper produced by a wet papermaking process.
[0023] Preferably, the non-woven fabric is polyester non-woven fabric; the paper produced by the wet papermaking process is a paper produced by a wet papermaking process after mixing one or more of cellulose-based fibers, chopped chemical fibers, glass fibers, and chopped carbon fibers.
[0024] Preferably, the conductive component in step (1) is a mixture of one or more of conductive carbon black, carbon nanotubes, and graphene; the polymer resin material is a mixture of one or more of acrylic resin aqueous dispersion, polyurethane resin aqueous dispersion, and vinyl acetate-ethylene copolymer emulsion; the organic crystal material is a mixture of one or more of paraffin, stearic acid, and palmitic acid; and the fiber material for wet papermaking is a mixture of one or more of cellulose-based fibers, short-cut polyester fibers, and glass fibers.
[0025] Specifically, the method for preparing the aqueous dispersion of the organic crystal material in step (2) comprises the following steps:
[0026] (2.1) Add the organic crystal material into a stainless steel reactor, add an emulsifier, control the reactor temperature to 80°C-90°C, melt the organic crystal material, and keep stirring for more than 10 minutes;
[0027] (2.2) Slowly add hot water at a temperature above 80° C. into the reaction kettle, keep stirring for more than 30 minutes, and cool for later use to prepare an aqueous dispersion of the organic crystal material.
[0028] Preferably, the emulsifiers are Tween 80 and Span 20, and the ratio of Tween 80 to Span 20 is 1:1 or 2:3 and 3:2.
[0029] Specifically, the method for preparing the aqueous dispersion of the conductive component in step (3) is: adding the conductive component to water and a dispersant, and physically dispersing the conductive component using one or a combination of ultrasound, a sand mill, and a high-speed disperser to prepare an aqueous dispersion of the conductive component; the method for preparing the aqueous dispersion of the wet papermaking fiber material in step (4) is: using a pulper to disperse the wet papermaking fibers in water to prepare an aqueous dispersion of the wet papermaking fiber material.
[0030] Preferably, in the preparation method of the aqueous dispersion of the fiber material for wet papermaking in step (4), chopped carbon fibers are also added, specifically, the fiber material for wet papermaking, chopped carbon fibers and water are added to a hydraulic pulper to prepare an aqueous dispersion of the fiber material for wet papermaking.
[0031] Preferably, in the step (5), the mixing ratio of the aqueous dispersion of the conductive component, the aqueous dispersion of the organic crystal material, the polymer resin material and the aqueous dispersion of the fiber material for wet papermaking is 5:80:25:2 to 10:80:25:2; and in the step (6), the papermaking machine is a papermaking machine with vacuum-assisted filtration molding.
[0032] The beneficial effects of the present invention are:
[0033] 1. The PTC electrothermal composite paper of the present invention adopts a double-layer structure design, which ensures the sheet resistance and PTC strength performance of the material on the one hand, and the mechanical strength of the material on the other hand.
[0034] 2. In the PTC electric heating composite paper structure, the conductive components include nano-scale powder materials (conductive carbon black, carbon nanotubes, graphene). At the same time, it can also include short-cut carbon fibers (which can be distributed in the second layer structure, or in the first layer structure, or in both layers). This kind of micron-millimeter scale conductive material (randomly distributed short-cut carbon fibers act like the bifurcated electrodes of the interdigitated electrodes in the prior art). This cross-scale material distribution can achieve lower sheet resistance while ensuring PTC strength (resistance change rate).
[0035] 3. In the PTC electrothermal composite paper structure, the second layer structure also includes fiber materials for wet papermaking and polymer resin materials. When the organic crystal material undergoes a phase change during the heating process of the PTC electrothermal composite paper, the fiber materials for wet papermaking and the polymer resin materials maintain a stable state and mechanical strength during the entire temperature change process. This effectively ensures the stability of the microstructure of the PTC electrothermal composite paper during use, thereby ensuring its service life.
[0036] 4. The material is prepared by papermaking machine. Papermaking process is a low-cost and large-scale process that can achieve low-cost manufacturing of materials.
[0037] 5. The preparation method disclosed in the present invention can adapt to the molding and manufacturing of materials of different scales and effectively ensure the comprehensive performance of the materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 It is a schematic diagram of the structure of the PTC electrothermal composite paper of the present invention;
[0039] Figure 2 This is a physical picture of the PTC electrothermal composite paper in Example 1 of the present invention;
[0040] Figure 3 This is a physical picture of the PTC electrothermal composite paper in Example 2 of the present invention;
[0041] Figure 4 This is a flow chart of the method for making PTC electrothermal composite paper of the present invention;
[0042] Figure 5 This is a schematic diagram of the equipment for continuously preparing PTC electrothermal composite paper according to the present invention;
[0043] Figure 6 is the PTC strength test curve in Example 1 of the present invention;
[0044] Figure 7 is the PTC strength test curve in Example 2 of the present invention;
[0045] Figure 8 is the PTC strength test curve in Example 3 of the present invention;
[0046] Fig. 9 is the PTC strength test curve in Example 4 of the present invention;
[0047] Fig.10 is the PTC strength test curve in Example 5 of the present invention;
[0048] Fig.11 It is the PTC strength test curve in comparative example 1 of the present invention;
[0049] Fig.12 It is the PTC strength test curve in comparative example 2 of the present invention.
[0050] The numbers in the figure are: 1-paper machine cylinder former, 2-first layer structure, 22-second layer structure, 11-vacuum port, 12-forming net, 13-edge sealing belt, 2-first layer structure, 21-unwinder, 3-paper machine slurry tank, 4-water absorption box, 5-dryer, 6-winder. DETAILED DESCRIPTION
[0051] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments.
[0052] Example 1: Figure 1 , 2 As shown in , 4, a PTC electric heating composite paper includes a first layer structure 2 and a second layer structure 22, the first layer structure 2 is a non-woven sheet material, specifically a polyester non-woven fabric, and the second layer structure 22 includes a conductive component, a polymer resin, an organic crystal material and a fiber material for wet papermaking.
[0053] A method for preparing PTC electrothermal composite paper comprises the following steps:
[0054] First, prepare an aqueous dispersion of organic crystal materials: (1) Add 10 kg of organic crystals stearic acid and palmitic acid into a stainless steel reactor, then add 1.2 kg of emulsifiers Tween 80 and Span 20 into the stainless steel reactor, control the temperature of the stainless steel reactor to 80°C, melt the organic crystals, and keep stirring for 20 minutes to fully mix the molten organic crystals and emulsifiers. (2) Keep the stainless steel reactor in a stirring state, slowly add 60 kg of 90°C pure water into the stainless steel reactor, keep stirring for 30 minutes, and cool to obtain an aqueous dispersion of organic crystal materials.
[0055] Prepare an aqueous dispersion of a conductive component: add conductive carbon black and a carbon black dispersant to pure water in a ratio of 10:1, then add them to a high-speed disperser (speed set at 4000 rpm) and disperse for 30 minutes to obtain a conductive carbon black dispersion; add carbon nanotubes and a carbon black dispersant to pure water in a ratio of 5:1, first use a high-speed disperser (speed set at 4000 rpm) to treat for 5 minutes, then pass through a horizontal sand mill twice to obtain a carbon nanotube dispersion; add graphene and a carbon black dispersant to pure water in a ratio of 5:1, then ultrasonically treat for 30 minutes to obtain a graphene dispersion; mix the conductive carbon black dispersion, the carbon nanotube dispersion and the graphene dispersion in a ratio of 10:1:1 to obtain an aqueous dispersion of a conductive component.
[0056] Preparation of aqueous dispersion of fiber material for wet papermaking: adding short-cut polyester fiber (mainly used to increase mechanical properties), short-cut carbon fiber and water into a hydraulic pulper, disintegrating for 30 minutes, and obtaining an aqueous dispersion of fiber material for wet papermaking.
[0057] Polymer resin material: In order to adapt to the papermaking process of the papermaking machine, the polymer resin material is selected in the form of a water dispersion of polymer resin (the polymer resin material is dispersed in water in the form of tiny particles). The water dispersion of the polymer resin is subjected to papermaking and forming, and the water is removed during the drying process to become a solid polymer resin. The polymer resin material is purchased directly from outside: the acrylic resin water dispersion can be purchased from Dow Rohm and Haas, the polyurethane resin water dispersion can be purchased from Wanhua Chemical, and the vinyl acetate-ethylene copolymer emulsion can be purchased from Guangxi Guangwei Chemical Co., Ltd. The function of the polymer resin material is to enhance the mechanical strength and maintain the stability of the microstructure of the PTC electrothermal composite paper. After the subsequent papermaking process, only the polymer resin is left. In this embodiment, the polymer resin material is formed by mixing the acrylic resin water dispersion and the vinyl acetate-ethylene copolymer emulsion in a ratio of 4:1.
[0058] The aqueous dispersion of the organic crystal material, the aqueous dispersion of the conductive component and the polymer resin material are first mixed and stirred evenly, and then the aqueous dispersion of the wet papermaking fiber material is added and stirred evenly to obtain a mixed slurry of the second layer structure 22 .
[0059] like Figure 5 The figure shows a large wrapped angle vacuum cylinder papermaking machine, in which the forming wire 12 is stretched on the cylinder former 1 of the papermaking machine, and the first layer structure 2 is a roll material, which is placed on the unwinder 21, and then the first layer structure 2 is pulled out and spread on the forming wire 12 through the guide roller. At the same time, the edge sealing belt presses the two edges of the first layer structure 2 onto the forming wire 12 to make the edges sealed. The paper machine cylinder screen former 1 rotates continuously, driving the forming screen 12 and the first layer structure 2 to operate continuously. At this time, the mixed slurry of the second layer structure 22 is continuously transported to the paper machine slurry tank 3; at the same time, the paper machine cylinder screen former 1 is evacuated through the vacuum port 11. Under the action of the vacuum suction force, a large amount of water in the mixed slurry of the second layer structure 22 is filtered out through the first layer structure 2, and the solid insoluble matter in the mixed slurry of the second layer structure 22 is retained on the surface of the first layer structure 2, and then further dehydrated through the water absorption box 4, and then thoroughly dried through the dryer 5 to obtain PTC electrothermal composite paper, and finally collected and wound by the winder 6. It should be noted here that the first layer structure 2 of this embodiment is specifically made of polyester non-woven fabric. The final PTC electrothermal composite paper structure is a two-layer structure, and the structural schematic diagram is shown in Figure 1 As shown, 2 is the first layer structure, 22 is the second layer structure. Figure 2 As shown, the light-colored side is the first layer structure 2 - polyester non-woven fabric, and the dark-colored side is the second layer structure 22 .
[0060] test:
[0061] (1) Sheet resistance test: a four-probe tester is used to test the sheet resistance of the PTC electric heating composite paper.
[0062] (2) A PTC electric heating composite paper is made into a 45cm*10cm electric heating sheet with an electrode spacing of 40cm. Two conductive wires are connected to a multimeter to test the real-time resistance value. The temperature of the entire electric heating sheet heat press machine is gradually increased from room temperature. The stable resistance value displayed by the multimeter at different temperatures is recorded. The resistance values at different temperatures are divided by the resistance values at room temperature to obtain the resistance change rate value (in %).
[0063] After testing, the square resistance of the PTC electric heating composite paper in this embodiment is 150Ω. Figure 6 As shown, from room temperature to 65 degrees Celsius, the resistance change rate is 660%.
[0064] Example 2: The preparation method of a PTC electrothermal composite paper in this example is mostly the same as that in Example 1, except that:
[0065] 1. The first layer structure 2 of this embodiment is specifically made of paper made of cellulose-based fibers (coniferous wood pulp is used in this embodiment), short-cut chemical fibers (short-cut polyester fibers are used in this embodiment) and short-cut carbon fibers using a wet papermaking process. The final PTC electric heating composite paper is a double-layer structure, and its structural schematic diagram is as follows Figure 1 As shown in the figure. Figure 3 As shown, the light-colored side is the first layer structure 2, which is paper made of softwood pulp, short-cut polyester fibers and short-cut carbon fibers using a wet papermaking process, and the dark-colored side is the second layer structure 22.
[0066] 2. Preparation of aqueous dispersion of fiber material for wet papermaking: Short-cut polyester fibers, cellulose-based fibers (coniferous wood pulp is selected in this embodiment) and water are added to a hydraulic pulper and dispersed for 30 minutes to obtain an aqueous dispersion of fiber material for wet papermaking.
[0067] 3. In this embodiment, the polymer resin material is prepared by mixing a polyurethane resin aqueous dispersion and a vinyl acetate-ethylene copolymer emulsion in a ratio of 4:1.
[0068] After testing, the square resistance of the PTC electric heating composite paper in this embodiment is 1000Ω. Figure 6 As shown, from room temperature to 65 degrees Celsius, the resistance change rate is 1200%.
[0069] Example 3: The preparation method of a PTC electrothermal composite paper in this example is mostly the same as that in Example 1, except that:
[0070] 1. The first layer structure 2 of this embodiment specifically uses paper made of short-cut chemical fiber and short-cut carbon fiber using a wet papermaking process. The final PTC electric heating composite paper is a double-layer structure. The specific physical diagram is similar to that of Example 2, so it is not given.
[0071] 2. Preparation of aqueous dispersion of organic crystal material: (1) Add 20 kg of palmitic acid into a stainless steel reactor, then add 1.2 kg each of emulsifiers Tween 80 and Span 20 into the stainless steel reactor, control the temperature of the stainless steel reactor to 85°C to melt the organic crystals, and keep stirring for 10 minutes to allow the molten organic crystals and emulsifiers to be fully mixed. (2) Keep the stainless steel reactor in a stirring state, slowly add 60 kg of 90°C pure water into the stainless steel reactor, keep stirring for 35 minutes, and cool to obtain an aqueous dispersion of organic crystal material.
[0072] 3. Prepare an aqueous dispersion of the conductive component: add conductive carbon black and carbon black dispersant to pure water in a ratio of 10:1, then add to a high-speed disperser (speed setting 4000 rpm), and disperse for 10 minutes to obtain an aqueous dispersion of the conductive component.
[0073] 4. Preparation of aqueous dispersion of fiber material for wet papermaking: Add cellulose-based fibers (broadleaf wood pulp is selected in this embodiment), short-cut carbon fibers and water into a hydraulic pulper and disintegrate for 35 minutes to obtain an aqueous dispersion of fiber material for wet papermaking.
[0074] 5. In this embodiment, the polymer resin material is an acrylic resin aqueous dispersion.
[0075] After testing, the square resistance of the PTC electric heating composite paper of this embodiment is 1200Ω / sq, and the resistance change rate from room temperature to 62 degrees Celsius is 3200% (such as Figure 8 ).
[0076] Example 4: The preparation method of a PTC electrothermal composite paper in this example is mostly the same as that in Example 1, except that:
[0077] 1. The first layer structure 2 of this embodiment is specifically made of paper made of short-cut carbon fiber and glass fiber using a wet papermaking process. The final PTC electric heating composite paper is a double-layer structure. The specific physical diagram is similar to that of Example 2, so it is not given.
[0078] 2. Preparation of aqueous dispersion of organic crystal material: (1) Add 10 kg of paraffin wax and palmitic acid into a stainless steel reactor, then add 1.2 kg of emulsifiers Tween 80 and Span 20 into the stainless steel reactor, control the temperature of the stainless steel reactor to 85°C to melt the organic crystals, and keep stirring for 15 minutes to fully mix the melted organic crystals and emulsifiers. (2) Keep the stainless steel reactor in a stirring state, slowly add 60 kg of 90°C pure water into the stainless steel reactor, keep stirring for 40 minutes, and cool to obtain an aqueous dispersion of organic crystal material.
[0079] 3. Prepare an aqueous dispersion of a conductive component: add graphene and a carbon black dispersant to pure water in a ratio of 5:1, and perform ultrasonic treatment for 35 minutes to obtain a graphene dispersion; add conductive carbon black and a carbon black dispersant to pure water in a ratio of 10:1, and then perform treatment with a high-speed disperser (4000 rpm) for 5 minutes to obtain a conductive carbon black dispersion; mix the conductive carbon black dispersion and the graphene dispersion in a ratio of 10:1 to obtain an aqueous dispersion of a conductive component.
[0080] 4. Preparation of aqueous dispersion of fiber material for wet papermaking: Add cellulose-based fibers (Tencel chopped fibers are selected in this embodiment), glass fibers and water into a hydraulic pulper and disintegrate for 40 minutes to obtain an aqueous dispersion of fiber material for wet papermaking.
[0081] 5. In this embodiment, the polymer resin material is prepared by mixing a polyurethane resin aqueous dispersion and a vinyl acetate-ethylene copolymer emulsion in a ratio of 4:1.
[0082] After testing, the square resistance of the PTC electric heating composite paper of this embodiment is 300, and the resistance change rate is 1000% (such as Fig. 9 ).
[0083] Example 5: The preparation method of a PTC electrothermal composite paper in this example is mostly the same as that in Example 1, except that:
[0084] 1. The first layer structure 2 of this embodiment is specifically made of paper made of glass fiber using a wet papermaking process. The PTC electric heating composite paper finally obtained has a double-layer structure. The specific physical diagram is similar to that of Example 2, so it is not given.
[0085] 2. Preparation of aqueous dispersion of organic crystal material: (1) Add 20 kg of stearic acid into a stainless steel reactor, then add 1.2 kg each of emulsifiers Tween 80 and Span 20 into the stainless steel reactor, control the temperature of the stainless steel reactor to 85°C, melt the organic crystals, and keep stirring for 15 minutes to fully mix the molten organic crystals and emulsifiers. (2) Keep the stainless steel reactor in a stirring state, slowly add 60 kg of 90°C pure water into the stainless steel reactor, keep stirring for 40 minutes, and cool to obtain an aqueous dispersion of organic crystal material.
[0086] 3. Prepare an aqueous dispersion of the conductive component: add conductive carbon black and carbon black dispersant into pure water at a ratio of 10:1, and then process with a high-speed disperser (4000 rpm) for 5 minutes to obtain an aqueous dispersion of the conductive component.
[0087] 4. Preparation of an aqueous dispersion of fiber material for wet papermaking: Add chopped polyester fibers, chopped carbon fibers and water into a hydraulic pulper and disintegrate for 40 minutes to obtain an aqueous dispersion of fiber material for wet papermaking.
[0088] 5. In this embodiment, the polymer resin material is vinyl acetate-ethylene copolymer emulsion.
[0089] After testing, the square resistance of the PTC electrothermal composite paper of this embodiment is 1300Ω / sq, and the resistance change rate is 3100% (such as Fig.10 ).
[0090] The square resistance of the PTC electric heating composite paper in the above five embodiments is much smaller than the square resistance of the PTC electric heating film on the market, while maintaining a good PTC strength. According to the data disclosed in patent 201910720440.7, its minimum square resistance is 4000Ω / sq, and it can be seen from Example 4 that its square resistance has increased from 7800Ω / sq to about 16000Ω / sq, and the resistance change rate is more than 200%. From this comparison, it can be seen that the present invention has achieved a good technical effect.
[0091] The experimental results are further explained below in combination with two comparative examples.
[0092] Comparative Example 1: The preparation method of a PTC electrothermal composite paper provided in this comparative example is mostly the same as that of Example 5, except that: an aqueous dispersion of a fiber material for wet papermaking is prepared: short-cut polyester fibers and water are added to a hydraulic pulper and dispersed for 40 minutes to obtain an aqueous dispersion of a fiber material for wet papermaking. That is, the first layer structure 2 and the second layer structure 22 do not contain short-cut carbon fibers.
[0093] After testing, the square resistance of the PTC electric heating composite paper of this embodiment is 6000Ω / sq, and the resistance change rate from room temperature to 70 degrees Celsius is 3500% (such as Fig.11 ). Although the resistance change rate is still relatively large, the sheet resistance is a bit too large, which shows that adding short-cut carbon fiber will have a better effect.
[0094] Comparative Example 2: The preparation method of a PTC electrothermal composite paper in this embodiment is mostly the same as that in Embodiment 1, except that: the second layer structure 22 does not contain fiber material for wet papermaking and polymer resin.
[0095] After testing, the square resistance of the PTC electrothermal composite paper of this embodiment is 130Ω / sq, and the resistance change rate is 650% (such as Fig.12 ). Although the square resistance is relatively small, only 130Ω / sq, and the resistance change rate is 650% at 65 degrees Celsius, Fig.12 As shown in the figure, after 65 degrees Celsius, the resistance gradually decreases, and at 120 degrees Celsius, the resistance change rate is only 280%. Such parameters are not conducive to the self-temperature control of PTC materials and lack of suitable media. This is due to the lack of fiber materials and polymer resins for wet papermaking. When the temperature exceeds the phase change temperature of organic crystals, the material gradually melts. At this time, the material lacks materials to support the microstructure, and the resistance is difficult to remain stable, but becomes smaller, resulting in a rapid decrease in the resistance change rate after the temperature is too high.
[0096] The specific implementation modes of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited to the above implementation modes, and various changes can be made within the knowledge scope of ordinary technicians in this field without departing from the purpose of the present invention.
Claims
1. A PTC electric heating composite paper, characterized in that: The invention comprises a first layer structure (2) and a second layer structure (22). The first layer structure (2) is a non-woven sheet material, and the second layer structure (22) comprises a conductive component, a polymer resin, an organic crystal material and a fiber material for wet papermaking.
2. The PTC electric heating composite paper according to claim 1, characterized in that: The second layer structure (22) also includes chopped carbon fiber material.
3. A method for preparing PTC electrothermal composite paper, characterized in that: The steps include: (1) preparing materials according to the following components: non-woven sheet material, conductive component, polymer resin material, organic crystal material and fiber material for wet papermaking; (2) preparing an aqueous dispersion of an organic crystalline material; (3) preparing an aqueous dispersion of a conductive component; (4) preparing an aqueous dispersion of a fiber material for wet papermaking; (5) mixing the aqueous dispersion of the conductive component, the aqueous dispersion of the organic crystal material, the polymer resin material, and the aqueous dispersion of the wet papermaking fiber material, and stirring them thoroughly to form a mixed slurry; (6) spreading the nonwoven sheet material on a forming wire of a paper machine; (7) Papermaking, the mixed slurry is transported to the surface of the non-woven sheet material, and under the vacuum suction force of the paper machine, the water in the mixed slurry is filtered out through the non-woven sheet material, and the solid insoluble matter in the mixed slurry is left on the surface of the non-woven sheet material; (8) Drying to remove residual moisture to obtain a PTC electric heating composite paper, which includes a first layer structure (2) and a second layer structure (22), the first layer structure (2) is a non-woven sheet material, and the second layer structure (22) includes a conductive component, a polymer resin, an organic crystal material and a fiber material for wet papermaking.
4. The method for preparing the PTC electrothermal composite paper according to claim 3, characterized in that: The non-woven sheet material in step (1) is non-woven fabric or paper produced by a wet papermaking process.
5. The method for preparing the PTC electrothermal composite paper according to claim 4, characterized in that: The non-woven fabric is polyester non-woven fabric; the paper produced by the wet papermaking process is a paper produced by a wet papermaking process using a mixture of one or more of cellulose-based fibers, chopped chemical fibers, glass fibers, and chopped carbon fibers.
6. The method for preparing the PTC electrothermal composite paper according to claim 3, characterized in that: In the step (1), the conductive component is one or a mixture of conductive carbon black, carbon nanotubes, and graphene; the polymer resin material is one or a mixture of acrylic resin aqueous dispersion, polyurethane resin aqueous dispersion, and vinyl acetate-ethylene copolymer emulsion; the organic crystal material is one or a mixture of paraffin, stearic acid, and palmitic acid; and the fiber material for wet papermaking is one or a mixture of cellulose-based fibers, short-cut polyester fibers, and glass fibers.
7. The method for preparing the PTC electrothermal composite paper according to claim 3, characterized in that: The method for preparing the aqueous dispersion of the organic crystal material in step (2) comprises the following steps: (2.1) Add the organic crystal material into a stainless steel reactor, add an emulsifier, control the reactor temperature to 80°C-90°C, melt the organic crystal material, and keep stirring for more than 10 minutes; (2.2) Slowly add hot water at a temperature above 80° C. into the reaction kettle, keep stirring for more than 30 minutes, and cool for later use to prepare an aqueous dispersion of the organic crystal material.
8. The method for preparing the PTC electrothermal composite paper according to claim 3, characterized in that: The method for preparing the aqueous dispersion of the conductive component in step (3) is: adding the conductive component to water and a dispersant, and physically dispersing the conductive component using one or a combination of ultrasound, a sand mill, and a high-speed disperser to prepare an aqueous dispersion of the conductive component; the method for preparing the aqueous dispersion of the wet papermaking fiber material in step (4) is: using a pulper to disperse the wet papermaking fibers in water to prepare an aqueous dispersion of the wet papermaking fiber material.
9. The method for preparing the PTC electrothermal composite paper according to claim 8, characterized in that: In the preparation method of the aqueous dispersion of the fiber material for wet papermaking in step (4), short-cut carbon fibers are also added, specifically: the fiber material for wet papermaking, short-cut carbon fibers and water are added to a hydraulic pulper to prepare an aqueous dispersion of the fiber material for wet papermaking.
10. The method for preparing the PTC electrothermal composite paper according to claim 3, characterized in that: In the step (5), the mixing ratio of the aqueous dispersion of the conductive component, the aqueous dispersion of the organic crystal material, the polymer resin material and the aqueous dispersion of the fiber material for wet papermaking is 5:80:25:2 to 10:80:25:2; and in the step (6), the papermaking machine is a papermaking machine with vacuum-assisted filtration molding.
Citation Information
Patent Citations
36V and below low-voltage driven PTC electrothermal film and preparation method thereof
CN110493900A